National identity in the modern education of Kazakhstan - Dossanova, Kamila K.; Kunekova, Tursyn M.; Zhumasheva, Gulzhan K.; Dossanova, Alma A. (Opción, 2019)
The paper provides an analysis and generalization of domestic and international experience on the issue of the effect of traditional music on the national identity formation. The study includes scientific methods of analysis and synthesis, abstraction, generalization of domestic and foreign experience in the musicological research tradition. People of different nationalities and religions co-exist peacefully on the same territory in the Republic of Kazakhstan. This situation is due to the policies pursued by the government, especially in the educational environment. Development and support of traditional music stimulate learning among the young generation on Russian history and culture.